'Look after the staff and they would look after the students' cultures of wellbeing and mental health in the university setting. Issue 4 (21st April 2022) - Brewster, Liz; Jones, Emma; Priestley, Michael; Wilbraham, Susan J.; Spanner, Leigh; Hughes, Gareth
ABSTRACT: University student wellbeing is increasingly seen as a concern, and as demands on university staff time for research, teaching, leadership and pastoral support also increase, this is mirrored in concerns about staff wellbeing. Dominant sectoral narratives frame student and staff wellbeing as oppositional, with initiatives to support student wellbeing positioned as creating additional practical and emotional demands on staff time and resources. Using a large qualitative dataset collected in the UK, including staff and students, this paper argues that that this does not have to be the case. Instead, there is a need to look beyond the provision of reactive services or isolated individual interventions, to proactively and cohesively embed cultural and structural change across the whole institution to support positive wellbeing outcomes for the whole university community. We report on the intrinsic interconnection between staff and student wellbeing; the importance of formal institutional policies in supporting or impeding staff and student wellbeing; access to training interventions to support staff and student wellbeing as a practical manifestation of these policies; and the impact of workplace culture and the centrality of compassion and community. The paper finds that it is important that institutions within higher education acknowledge and respond proactively to both staff and student wellbeing issues. To do so, institutions should seek to foster a sustainable and effective academic environment with a whole university approach.